Dispute Settlement for ASEAN Businesses under the Belt and Road Initiative: New Possibilities and Directions - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2022)
This forward-looking book examines dispute resolution issues in the context of Belt and Road Initiative dealings between parties in ASEAN Member States, China and other trade partners. It discusses a range of commercial dispute issues and economic agreements including free trade agreements and investment agreements, both bilateral and regional.